Topography of toxin-acetylcholine receptor complexes by using photoactivatable toxin derivatives. - Chatrenet, B (1990)
We have defined the molecular environment of a snake neurotoxin interacting with the high- and low-affinity binding sites of the nicotinic acetylcholine receptor (AcChoR). This was done by photocoupling reactions using three toxin derivatives with photoactivatable moieties on Lys-15, Lys-47, and Lys-51. Competition data showed that Lys-47 belongs to the toxin-AcChoR interacting domain whereas the other two residues are excluded from it. We first tentatively determined the threshold of covalent coupling, indicative of the proximity between the photoactivatable probes and subunits, by quantifying the coupling occurring between the same derivatives and a model compound (i.e., a toxin-specific monoclonal antibody). We then (i) quantified the coupling yields occurring when both binding sites of AcChoR were occupied by the toxin derivatives, (ii) discriminately quantified the coupling yields at the high-affinity binding site, and (iii) deduced the coupling yields at the low-affinity binding site. In the high-affinity site, the probes on Lys-15 and Lys-47 predominantly reacted with the high-affinity site of the AcChoR alpha subunit whereas the probe on Lys-51 reacted with the delta subunit. In the low-affinity site, the probe on Lys-47 predominantly reacted with the low-affinity site of the alpha chain and the beta chain whereas those on Lys-15 and Lys-51 reacted with the gamma and delta chains, respectively. A three-dimensional model showing a unique organization of AcChoR bound to two toxin molecules is presented.